Rooting for Rafael Rosales - Scaletta, Kurtis (Albert Whitman & Company, 2018)
A young man from the Dominican Republic who dreams of playing professional professional baseball in the United States crosses paths with a young environmentalist from Minneapolis who is passionate about saving bees.